Designing with Indigenous Knowledge: Turning Five Learning Principles into Implementable Curriculum Decisions - Ebenezer Omolafe Babalola; Eyiyemi Veronica Omolafe (International Journal of Ethnoscience and Technology in Education, 2026)
Education for Sustainable Development (ESD) increasingly emphasizes sustainability competencies (SCs), yet the educational pathways proposed to cultivate them often rest on implicit worldview assumptions that can marginalize Indigenous Knowledge (IK) and other epistemologies. This commentary/conceptual synthesis argues that the central challenge is not the absence of guiding principles but the limited translation of principles into implementable curriculum decisions that can be documented and reviewed. It proposes a minimum decision framework that makes curriculum design more traceable, evaluable, and improvable by linking learning principles to explicit decisions across four domains: selection (which competencies and IK domains are prioritized), authority (who validates, represents, and limits knowledge use), activity design (how engagement and pedagogy enact the principles), and assessment (what evidence counts as demonstrated competence and how it is judged). Two areas are emphasized as essential for curricular accountability: knowledge governance, to protect epistemic integrity and reduce tokenistic or extractive uses of IK, and assessment evidence logic, to recognize process-based demonstrations of competence without flattening plural worldviews. The core claim is that closing the education–reality gap depends on auditable decision logics and evidence practices, not principles alone.